By evening's light - Gould, Leslie, 1962- (Gould, Leslie, 1962- Amish memories, 2024)
"Heartbroken after a failed relationship, Treva Zimmerman returns to Lancaster County to visit her Amish relatives before leaving her Plain past behind her for good. While caring for her elderly Aunt Rosene, Treva finds inspiration in her aunt's story of a dramatic trip to Cold War Germany--but is it enough to change her plan?"--